An efficient 3-acylquinoline synthesis from acetophenones and anthranil via C(sp3)–H bond activation mediated by Selectfluor. Issue 18 (2nd April 2019) - Gao, Yejun; Hider, Robert C.; Ma, Yongmin
Abstract : An efficient method for the synthesis of 3-functionalized quinolines from acetophenones and anthranil mediated by Selectfluor was achieved. Abstract : An efficient method for the synthesis of 3-functionalized quinolines from commercially available acetophenones and anthranil has been described. Selectfluor propels the C(sp 3 )–H bond activation of the acetophenones and aza-Michael addition of anthranil resulting in annulated 3-acylquinolines in moderate to high yields. DMSO acts not only as a solvent but also as a one carbon donor in the reaction.